2020
DOI: 10.1002/advs.201903392
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation by Design: Using Topography to Control Human Monocyte Attachment and Macrophage Differentiation

Abstract: Macrophages play a central role in orchestrating immune responses to foreign materials, which are often responsible for the failure of implanted medical devices. Material topography is known to influence macrophage attachment and phenotype, providing opportunities for the rational design of “immune‐instructive” topographies to modulate macrophage function and thus foreign body responses to biomaterials. However, no generalizable understanding of the inter‐relationship between topography and cell response exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 45 publications
1
115
0
Order By: Relevance
“…To be specific, many reports have demonstrated that the biophysical clues such as the surface topography which the macrophages grow on is critical for polarization regulation. [4][5][6] Our previous studies also indicate that the micro/nano topography of TiO 2 nanotubular surface with ~30 nm diameter is able to induce M2 polarization and consequently influence the osseointegration in vivo. 7,8 This phenomenon has not only provided a more convenient and safe way to induce M2 polarization, but has also led to the concept of "osteoimmunity" during the designation of bone implant.…”
Section: Introductionmentioning
confidence: 87%
“…To be specific, many reports have demonstrated that the biophysical clues such as the surface topography which the macrophages grow on is critical for polarization regulation. [4][5][6] Our previous studies also indicate that the micro/nano topography of TiO 2 nanotubular surface with ~30 nm diameter is able to induce M2 polarization and consequently influence the osseointegration in vivo. 7,8 This phenomenon has not only provided a more convenient and safe way to induce M2 polarization, but has also led to the concept of "osteoimmunity" during the designation of bone implant.…”
Section: Introductionmentioning
confidence: 87%
“…Macrophages will express diverse genes and inflammatory cytokines on the surfaces with different roughness and topology, resulting in significant effects on the inflammatory response and the FBR. [ 165–169 ] A biomaterial with a smooth surface usually induce lower inflammatory response, [ 170,171 ] which is a consensus about the design of implantable materials. However, Rosengren et al.…”
Section: Conventional Strategies To Migrate the Fbrmentioning
confidence: 99%
“…Another example of an available high throughput approach is the TopoChip platform, which allows mathematically defined surface topographies to be screened for their influence on cellular responses. [141,148] As already validated for human macrophages, the combination of this platform with machine learning algorithms can lead to rapid identification of optimal immuneinstructive biomaterial surfaces. [148] Michiel Croes completed his Ph.D. on the use of osteo-immunomodulation to improve the bioactivity of ceramics.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…[141,148] As already validated for human macrophages, the combination of this platform with machine learning algorithms can lead to rapid identification of optimal immuneinstructive biomaterial surfaces. [148] Michiel Croes completed his Ph.D. on the use of osteo-immunomodulation to improve the bioactivity of ceramics. Currently, he is a postdoctoral researcher in the Department of Orthopedics at the University Medical Center Utrecht.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation